Educational and support materials for family caregivers of people with mental disorders: integrative review (Research, Society and Development, 2022)
This article aims to summarize studies that address educational and support materials and educational technologies for caregivers of people with mental disorders. This is an integrative review, with the research question: “What has been published in the scientific databases on educational and support materials for family members of people with mental disorders?”. We conducted the search using the PICO strategy between September and October 2021, in the following databases: Web of Science, Nursing Database (BDENF), Latin American and Caribbean Health Sciences Literature (LILACS), SciVerseScopus, and Medical Literature Analysis and Retrieval System Online (MEDLINE). Five articles were included following the PRISMA methodology. The studies showed that the quality of life of caregivers of people with mental disorders is affected, therefore, modern technologies are used as a methodology to support caregivers of patients with mental disorders. This study proved to be compatible with reality, the caregiver's health is left aside. This finding demonstrates that this sector is somewhat neglected in the incorporation of technologies for prevention. We reflect on the need for strategies to prevent illnesses of caregivers of people with mental disorders.